“All Parts are to Be Reformed...”: To the History of the Combat Path of the 8th Motor Rifle Division of the Internal Troops of the NKVD (July 1942) - Maxim Strelnikov (Вестник Волгоградского государственного университета. Серия 4. История, регионоведение, международные отношения)
Introduction. The participation of the Internal Troops of the NKVD in the Great Patriotic War is a well-known phenomenon. They were used throughout the entire conflict. However, despite the fame and significance, including practical, of the topic, it can hardly be called fully studied. Thus, the issue of the use of the Internal Troops of the NKVD in the Battle of Stalingrad is an important scientific study, but most of the research is devoted only to the 10th Rifle Division of the Internal Troops of the NKVD. However, as the author managed to establish, in addition to this formation, the Stalingrad Front also included the 8th Motor Rifle Division of the Internal Troops of the NKVD. This is the issue covered in the article. Methods and materials. The study used general scientific and specific scientific methods. The materials of the Central Archive of the Ministry of Defense of the Russian Federation were used. All sources by type are written and are represented by the following type groups: office work and accounting documentation, reference materials. Analysis. An analysis of the works of domestic authors has shown that the experience of the 8th Motor Rifle Division of the Internal Troops of the NKVD in the Great Patriotic War is of little interest to researchers. Only individual episodes of the unit’s participation in some battles are reflected in historiography. The study examines the issue of the participation of the 8th Motor Rifle Division of the Internal Troops of the NKVD in combat operations and its withdrawal from them during the first half of July 1942, when the unit will be included in the forming Stalingrad Front. Results. It was revealed that the unit had serious problems with the provision of material and technical equipment and staffing. The author established the reasons for these issues. It was also possible to trace in detail the entire combat path of the 8th Motor Rifle Division of the Internal Troops of the NKVD for the specified period, down to individual units from the main and attached composition. Statistical data on the composition, losses, and provision of the material and technical base of the unit are presented in tabular form.